PENYUSUNAN INSTRUMEN TES FORMATIF FISIKA SMP - Rohayati, Isnaini; Siti Aminah, Nonoh; Yusliana Ekawati, Elvin (Jurnal Pendidikan Fisika, 2013)
The aim of this research was to apprehend the characteristics of physics formative test instrument which has been arranged. This research was a basic research. The research had been doneÂ  in Surakarta and Girimarto involved respondent of students of class VIII A, B, C, D, E, F, and G SMP Negeri Girimarto on educational year 2011/2012. The test that had been arranged was a formative test of light matter. Data gathering was done by non-test technique and test technique. Data analysis technique that was used was qualitative analysis with problem study and quantitative technique with multiple choices problem analysis covered difference capacity, difficulty level, distractor effectivity, and problem reliability. The research finding was a qualitative study result by expert. From the qualitative study, it was obtained that many problems need to be revised since the answer choice were not alphabetical, uneffective sentences, and inappropriate matter . The result of field test I showed as follow: packet A: there were 6 problems of difficult category, 24 problems of medium category, and 10 complicated problems, from the difference capacity, there were 5 problems that had negative difference capacity, 5 problems were poor, 5 problems were satisfactory, 13 problems were good, and 12 problems were excellent. For the packet B problems, there were 13 difficult problems, 23 problems were medium, and 4 problems were easy. There were 12 problems rejected, 1 problems was poor, 4 problems were satisfactory, 15 problems were good and 10 problems were excellent based on the difference capacity. From the research finding, it could be be concluded that the arrangedÂ  test was âtes Formatif FisikaSMP Materi Cahaya, Tahun Pelajaran2011/2012â. The test was an objective test in multiple choices form with four answer choices of 50 problems. Time allocation of test doing was 90 minutes. The arranged test was equippedÂ  by direction how to do and key answer. Characteristics of arranged test were packet A problems with 25% easy category, 60% medium category, and 15% difficult category. From the difference capacity, it was obtained that problems with excellent Â difference capacity were 30%, good were 32,5%, satisfactory were 12,5%, poor were 12,5%, and rejected were 12,5%. From the effectivness distractor aspect, it was obtained that 85% of problems were four distractors functioned, and 15% problems were 3 distractors functioned, 0% problems were two distractors functioned, and 0% problems were one distractors functioned. Packet B problems, there were 10% of easy category, 57,5% of medium category, and 32,5% of difficult category. Based on the difference capacity, the problems withÂ  excellent were 25%, good were 32,5%, satisfactory were 10%, poor were 2,5%, and rejected were 30%. Whereas from the effectiveness distractors aspect, it was acquired that 85% of problems were four distractors funtioned, and 12,5% problems were 3 distractors functioned, 2,5%Â  problems were two distractors functioned, and 0% problems were one distractor funtioned. FromÂ  the last test instument, it was attained that there were 22% of easy category, 54% of medium category, and 24% difficult category. Problems with excellent difference capacity were 10%, good were 36%, satisfactory were 28%, poor were 18%, and rejected were 8%. From the effectiveness distractor aspect, it was gained thatÂ  68% problems were four distractors functioned, and 28% problems were 3 distractors functioned, 4% problems were two distractors functioned, and 0% problems were one distractor functioned. From the three packet of test, the test that had the best quality and characteristics was the last test. Key words: Test arrangement, Formative test, Cognitive aspect.